2023
DOI: 10.1007/s11628-023-00524-0
|View full text |Cite
|
Sign up to set email alerts
|

Are customer star ratings and sentiments aligned? A deep learning study of the customer service experience in tourism destinations

Abstract: This study explores the consistency between star ratings and sentiments expressed in online reviews and how they relate to the different components of the customer experience. We combine deep learning applied to natural language processing, machine learning and artificial neural networks to identify how the positive and negative components of 20,954 online reviews posted on TripAdvisor about tourism attractions in Venice impact on their overall polarity and star ratings. Our findings showed that sentiment vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In the destination context, electronic word‐of‐mouth has been defined as informal communications made by tourists to inform others about the characteristics and use of tourism services and their providers through the internet (i.e., online platforms enabling social interaction, integrated tourism websites, social networks) (Litvin et al, 2018). Past studies have identified references to crowding in travel‐focused electronic word‐of‐mouth (Bigné et al, 2023; Buzova et al, 2019, 2020; Zanibellato et al, 2018). For example, in the cruise ship destination context, Buzova et al (2019) showed that visitors who perceive crowding during their visits tend to make unfavorable comments about their experiences on social media and integrated tourism websites (e.g., discouraging visits to the port of call, or certain attractions).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the destination context, electronic word‐of‐mouth has been defined as informal communications made by tourists to inform others about the characteristics and use of tourism services and their providers through the internet (i.e., online platforms enabling social interaction, integrated tourism websites, social networks) (Litvin et al, 2018). Past studies have identified references to crowding in travel‐focused electronic word‐of‐mouth (Bigné et al, 2023; Buzova et al, 2019, 2020; Zanibellato et al, 2018). For example, in the cruise ship destination context, Buzova et al (2019) showed that visitors who perceive crowding during their visits tend to make unfavorable comments about their experiences on social media and integrated tourism websites (e.g., discouraging visits to the port of call, or certain attractions).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in the cruise ship destination context, Buzova et al (2019) showed that visitors who perceive crowding during their visits tend to make unfavorable comments about their experiences on social media and integrated tourism websites (e.g., discouraging visits to the port of call, or certain attractions). Bigne et al (2023) also showed that negative online reviews about a destination were based mainly on perceptions of crowding or overcrowding. Based on the above evidence, we propose the following hypothesis:…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is proven ratings and reviews are significantly important to both businesses and customers during their purchases, but companies are losing sales, profits, and valuable information without ratings and reviews as their research demonstrated in the diagram below [55]. Similarly, results show a relationship between star rating and sentiments using deep learning via natural language processing, machine learning, and artificial neural networks [56].…”
Section: B Usefulness In Salesmentioning
confidence: 99%
“…Apart from analyzing textual reviews, ratings and emojis have been of interest in deriving users' thoughts and emotions towards mobile apps. Bigne et al (2023) were concerned to find if the star ratings and the sentiment of the review of a customer are related. Although the results reveal that the star rating aligns with the overall sentiment of the review, the authors consider that there can be different dimensions of customer experience in a specific service.…”
Section: Related Workmentioning
confidence: 99%
“…By manual observation, it was revealed that, most of the neutral reviews were biased towards the negative or positive polarity. As (Bigne et al, 2023) mention, although consumers place a star rating as 3, in the review, either the positive or negative aspects get canceled out or the consumer gets biased towards a certain dimension which he is interested in discussing more about. Besides, there were entries where the sentiment of the text content is gainsaid to the sentiment of the rating.…”
Section: Labeling the Datamentioning
confidence: 99%